Deficiency of the eighth component of complement associated with recurrent meningococcal meningitis: case report and literature review - Daniela Dornelles Rosa; Alessandro C. Pasqualotto; Maurício de Quadros; Sérgio Henrique Prezzi (Brazilian Journal of Infectious Diseases)
The authors report a case of deficiency of the eighth component of complement in a young adult with a history of three episodes of meningitis; one of them proved to be meningococcal. The literature was reviewed and meningitis due to Neisseria meningitidis strains causing disease in complement-deficient and complement-sufficient patients was demonstrated. Meningococcal disease may be the first manifestation of complement deficiency; screening for complement function must be considered for those with invasive meningococcal disease, with posterior evaluation of the components of the terminal pathway of complement.